The Effect of Business Cycles on Health Expenditure: A Story of Income Inequality in China - Pu, Xiaohong; Zeng, Ming; Luo, Yaling (Frontiers in Public Health, 2021)
Using the panel data of 31 regions in China from 2001 to 2018, this study aims to investigate the effect of business circles on health expenditure from the role of income inequality. We find that health expenditure experiences a change from pro-cyclical to counter-cyclical with business circles. Specifically, business circles have a different influence on health expenditure before and after the financial crisis in 2008. Our findings also show that income inequality can moderate the impact of business circles on health expenditure in China. More importantly, the role of income inequality in the above issue varies from different regions. We conclude that the government should try to take active steps to control health expenditure by decreasing income inequality.